Implementación piloto de la gestión integral de la farmacoterapia a pacientes hospitalizados con enfermedades cardiovasculares - Maraelys Morales González; Evelyn I. Rojas Vázquez; Lizandra Fuentes de la Torre; Beltis Villanona Pons; Niurka M. Dupotey Varela (Journal of Pharmacy & Pharmacognosy Research, 2024)
Context: Comprehensive medication management service provides comprehensive pharmaceutical care to patients to meet their pharmacotherapeutic needs and improve their quality of life in terms of health.